2017
DOI: 10.1017/s1744133116000335
|View full text |Cite
|
Sign up to set email alerts
|

The effects of payments for pharmaceuticals: a systematic literature review

Abstract: The existence of different forms of out-of-pocket payments (OOPs) for pharmaceuticals across the globe provokes the question whether they can achieve more negative or positive consequences. A systematic literature review was conducted to assess the association between drug cost sharing and health care services utilization, health care costs as well as health outcomes. Studies published in The Cochrane Library, PubMed, Embase were searched with such keywords as: drug, pharmaceutical, cost sharing, out of pocket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“… - no ‘a priori’ design; - grey literature not searched; - list of excluded studies not provided; - formal quality assessment of included studies poorly described and discussed; - results may not be generalizable to other chronic conditions not included. Kolasa, Kowalcyzk, 2019 [ 50 ] - Narrative review (systematic) - General population - Health Economics, Policy and Law Association between prescription drug cost-sharing and health care consumption and health outcomes. - drug use: no - healthcare use: yes - health: yes - a priori’ design: yes - search comprehensive: yes - grey literature: no - year of last search: 2016 - # of studies included: total, 18; drugs/cost-sharing/ins, 18; Canada, 2 - duplicate study selection and data extraction: yes Used a checklist, adapted from Gardner, Machin, Campbell (1986), for the assessment of the statistical content of medical studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… - no ‘a priori’ design; - grey literature not searched; - list of excluded studies not provided; - formal quality assessment of included studies poorly described and discussed; - results may not be generalizable to other chronic conditions not included. Kolasa, Kowalcyzk, 2019 [ 50 ] - Narrative review (systematic) - General population - Health Economics, Policy and Law Association between prescription drug cost-sharing and health care consumption and health outcomes. - drug use: no - healthcare use: yes - health: yes - a priori’ design: yes - search comprehensive: yes - grey literature: no - year of last search: 2016 - # of studies included: total, 18; drugs/cost-sharing/ins, 18; Canada, 2 - duplicate study selection and data extraction: yes Used a checklist, adapted from Gardner, Machin, Campbell (1986), for the assessment of the statistical content of medical studies.…”
Section: Resultsmentioning
confidence: 99%
“… Drug use: socioeconomic status, chronically ill Among the poor and chronically ill, higher cost-sharing was associated with lower drug use [ 17 , 23 , 27 ]; – Own-price η, poor ≈ − 0.05 to − 0.4; based on aggregate data [ 24 ]; – Own-price η, poor ≈ − 0.03 to − 0.2; based on individual/household data [ 24 ]; – Own-price η, poor/chronically ill ≈ − 0.3 to − 0.5 [ 17 ]; Vulnerable populations were more responsive to cost-sharing than non-vulnerable population [ 37 ]; Among individuals with cardiovascular-related chronic disease, drug insurance was associated with increased adherence and persistence to medications [ 38 , 42 ]; Among individual with hypertension lower drug cost-sharing was associated with hypertension treatment [ 34 ]; Statin users required to make a copayment were more likely than others to be nonadherent [ 33 ]; Higher cost-sharing was associated with lower use of specialty drugs indicated for rheumatoid arthritis (RA), multiple sclerosis (MS), and cancer [ 43 ]. Health services use: general population Limiting (expanding) drug insurance was associated with an increase (decrease) in the use of health services (emergency department visits, emergency mental health service, hospitalizations, psychiatric hospitalizations, nursing home admissions [ 39 ]; Higher levels of prescription drug cost-sharing were associated with lower use of health services: – Outpatient visits [ 24 , 32 , 37 , 50 ]; – Preventative services [ 32 ]; – Emergency department visits [ 24 , 25 , 32 , 37 , 50 ...…”
Section: Resultsmentioning
confidence: 99%
“…Their review identified 47 eligible studies on the behavioral effects of copayment, and the majority of their reviewed studies suggested that copayments reduce outpatient care utilization [10]. Recent systematic literature reviews, such as Kolasa and Kowalczyk [11] and Sensharma and Yabroff [12], investigating the relationships between patient cost-sharing of prescription drugs, healthcare utilization and health outcomes, suggested that an increase in patient cost-sharing of prescription drugs not only decreases prescription drug utilization, but also increases the risk of worsening health outcomes (in terms of deteriorating adherence to prescription drugs), and increases the demand for healthcare services, such as the emergency room, outpatient services and inpatient care services. Another strand of the literature, on the effect of user fee (consisting of copayment and cost-sharing) changes on healthcare utilization, applied a difference-in-differences (DID) regression model to evaluate the effect of user fees on the utilization of various healthcare services.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…quasiexperimental analytical approaches. As outcomes, studies have mainly examined effects on public pharmaceutical spending and medicine utilization [21][22][23][24][25][26][27][28]. Evidence fairly consistently shows that increases and introductions of cost sharing for medicines reduces their utilization, with effects extending to necessary medications, and particularly affecting vulnerable groups.…”
Section: Introductionmentioning
confidence: 99%